Does exercise training improve physical fitness and health in adult liver transplant recipients? A systematic review and meta-analysis - De Smet, S; O’Donoghue, K; Lormans, M; Monbaliu, D; Pengel, L (Lippincott, Williams & Wilkins, 2022)
Background: The impaired physical fitness of end-stage liver disease patients often persists after liver transplantation (LT) and compromises posttransplant recovery. This systematic review and meta-analysis evaluated evidence supporting the potential of exercise training to improve physical fitness and health-related quality of life (HRQOL) after LT. Methods: Bibliographic searches identified all randomized controlled trials (RCTs) comparing aerobic and strength training versus usual care after LT. Risk of bias was assessed, and study outcomes measuring physical fitness and HRQOL were extracted. Meta-analysis was performed if at least 3 studies reported on an outcome. Results: Eight RCTs (n = 334) were identified. Methodological study quality varied and was poorly reported. Meta-analyses showed a trend for favorable effects of exercise on cardiorespiratory fitness (peak oxygen uptake or 6-min walking distance; 6 studies, n = 275; standardized mean difference: 0.23, 95% confidence interval [CI], −0.01 to 0.48) and of strength training either or not combined with aerobic training on muscular fitness (dynamometry-assessed muscle strength or 30-s sit-to-stand test; 3 studies, n = 114; standardized mean difference: 0.34, 95% CI, −0.03 to 0.72). A favorable effect was found for exercise on the Short-Form Health Survey-36 HRQOL physical function subcomponent (3 studies, n = 194; mean difference: 9.1, 95% CI, 0.3-17.8). No exercise-related adverse events were observed. Conclusions: RCTs indicate that exercise training in LT recipients is safe, improves physical function aspects of HRQOL, and may benefit cardiorespiratory and muscular fitness. The strength of evidence is, however, limited by the low number of patients and study quality. More adequately powered, high-quality RCTs are warranted.